TEKSTUR DAN BAHAN ORGANIK TANAH SERTA HUBUNGANNYA DENGAN BATAS ATTERBERG DAN AKTIVITAS LIAT - Nazilia Indana Zulfa; Cahyoadi Bowo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Clay minerals are an important indicator of soil plasticity, influencing clay activity. This study aimed to elucidate the effect of clay minerals, organic C and primary minerals on the Atterberg limit and clay activity. The study was conducted in the Kemuning sub-watershed, Jember, East Java. The study began by preparing a thematic map to determine sample points with stratified random sampling. They were taken as many as 35 disturbed soil sample points at 0-20 cm from the surface. Soil texture was determined using the pipette method, and organic C was determined by the spectrophotometer method. The liquid limit and plastic limit were used to determine the plasticity index. A microscopic analysis of sand mineralogy was carried out to compare activity values with a magnification of 20-40 times to assess the primary soil minerals. The results showed that clay and C-organic affect fluidity, plastic limit, and plasticity index. The presence of andesine, albite, olivine, and orthoclase in the sand fraction and the low clay activity indicated that kaolinite dominated the study area, with smaller amounts of illite and halloysite.